Development of Transport in Eastern Regions of Russia - Tsvetkov, Konstantin; Slepov, Vladimir; Sekerin, Vladimir; Gayduk, Vladimir; Gorokhova, Anna (International Journal of Engineering and Technology, 2018)
This article considers the issues on forming the Russian transport system, and the impact of distance and climate on the transport development. Special attention is paid to the role of railway transport in the countryâ€™s transport system, the state and development of rolling stock, and the development of track equipment. Considerable attention is paid to the development of transport and the railway network in the Far East and Siberia.Â